ANALISIS PERBANDINGAN PRAKTIK AKUNTANSI TRANSAKSI MUDHARABAH DAN MUSYARAKAH DENGAN PSAK N0 105 DAN 106 DI BMT DANA INSANI - Widarusamsi, Fadhilah Puji; Hidayah, Khusnul (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2013)
Islamic Bank or that is widely knew as sharia Bank has been growth significantly in Indonesia. However, it has not been distributed to all society. Then the existing of BMT is able to reach the middle lower society. The accounting standard that based on the sharia principles is the key system on the bank or the sharia principles is the key system on the bank or the sharia finance institution. The application of PSAK sharia has been the obligatory in this institution due to the significant growth of this finance industry. PSAK related to mudharabah and musyarakah is defined in PSAK No.105 regarding musyarakah accounting. The research objective of this research was to examine the accounting treatment over the mudharabah and musyarakah transaction on the BMT Dana Insani, to compare the differences of the concordance between mudharabah accounting transaction treatment on the BMT with the provision of PSAK No.105 and to compare the difference of the concordance between musyarakah accounting treatment on the BMT with the provision of PSAK No.106. Mudharabah and musyarakah would be proxy by including recognition, measurement, disclosure and presentation. The object of the research was BMT Dana Insani. Meanwhile the data being applied were the primary data and secondary data. The data collecting technique were interview and documentation. The analysis data method were carried out with the qualitative descriptive then being analyzed applying the comparative data, that is by comparing between the mudharabah and musyarakah transaction treatment on BMT Dana Insani with the provision of PSAK. The result of the research can be concluded that the application of the mudharabah and musyarakah accounting transaction treatment on the BMT Dana Insani, generally, has been in conformity with the PSAK No.105 regarding to the recognition, measurement, disclosure, and presentation. However, there were some transaction that the recording has not been confirmed with the provision of PSAK No.105 and 106.